2014
DOI: 10.1186/s13075-014-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of synthetic microRNA-210 accelerates avascular meniscal healing in rat medial meniscal injured model

Abstract: IntroductionThe important functions of the meniscus are shock absorption, passive stabilization and load transmission of the knee. Because of the avascularity of two-thirds of the meniscal center region, the treatment of tears in this area is hard. Recently, microRNAs have been proven to play an important role in the pathogenesis of diseases. We focused on microRNA (miR)-210, which plays a wide spectrum of roles comprising mitochondrial metabolism, angiogenesis, DNA repair and cell survival. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…MicroRNA acts through posttranscriptional regulation of target genes, leading to the degradation of target gene mRNAs or translational inhibition. The results from this study and previous studies showed increased VEGF and STAT3 expression when miR‐210 was overexpressed . Consequently, we hypothesized that VEGF and STAT3 may not be direct targets of miR‐210.…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…MicroRNA acts through posttranscriptional regulation of target genes, leading to the degradation of target gene mRNAs or translational inhibition. The results from this study and previous studies showed increased VEGF and STAT3 expression when miR‐210 was overexpressed . Consequently, we hypothesized that VEGF and STAT3 may not be direct targets of miR‐210.…”
Section: Resultssupporting
confidence: 48%
“…The findings confirmed that miR‐210 expression increased in both hypoxic brain tissue and EPCs. The overexpression of miR‐210 in endothelial cells in vitro promoted the formation of capillary‐like structures, and the local injection of miR‐210 promoted vascular proliferation in injured joints, the Achilles tendon, and the myocardium . The overexpression of miR‐210 in the striatum by local injection of lentivirus was previously shown to enhance angiogenesis in the basal ganglia and neurogenesis in the SVZ and hippocampus of both normal and cerebral ischemia mice .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a recent study demonstrated that intraarticular delivery of an antagonist of miR-483-5p (previously identified as overexpressed in OA chondrocytes) delayed the progression of OA in mice using the DMM post-traumatic model, specifically by modulating matrilin 3 and tissue inhibitor of metalloproteinase 2 (TIMP-2) [72]. A second study published in 2014 examined intraarticular injection of miRNA-210 in partially transected anterior cruciate ligaments of rats and found increased healing by the enhancement of angiogenesis through upregulation of VEGF and FGF2 expression, along with increases in transcription of Col2a1 [73]. Despite tissue evidence of miRNA dysregulation in OA, a very recent study in mice failed to identify a circulating serum miRNA profile associated with early OA damage [74].…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…The same technique has also produced a desired effect in accelerating avascular meniscal healing in rat medial meniscal injured model [132]. Since oligonucleotides or virus based constructs can systemically reintroduce a tumour-suppressor miRNA into cancer cells so as to repress tumour growth [133], miR-210 may be a favorable future treatment approach for ESCC patients.…”
Section: A Promising Therapeutic Target For Mir-210mentioning
confidence: 99%